2023
DOI: 10.1111/anae.15983
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of dexmedetomidine for delirium in adults undergoing heart valve surgery

Abstract: Dexmedetomidine might reduce delirium after cardiac surgery. We allocated 326 participants to an infusion of dexmedetomidine at a rate of 0.6 lg kg À1 for 10 min and then at 0.4 lg.kg À1 .h À1 until the end of surgery; 326 control participants received comparable volumes of saline. We detected delirium in 98/652 (15%) participants during the first seven postoperative days: 47/326 after dexmedetomidine vs. 51/326 after placebo, p = 0.62, adjusted relative risk (95%CI) 0.86 (0.56-1.33), p = 0.51. Postoperative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our data may partially explain the findings of Wang et al., which showed an increased risk of postoperative AKI in patients undergoing cardiac surgery [9]; but the harm signal in this study was statistically fragile and seemed to be driven by stage 1 AKI, limiting clinical significance. In our study, we found no differences in renal macro‐ or microcirculatory perfusion or oxygenation that could explain the increased incidence and severity of histological renal tubular injury.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our data may partially explain the findings of Wang et al., which showed an increased risk of postoperative AKI in patients undergoing cardiac surgery [9]; but the harm signal in this study was statistically fragile and seemed to be driven by stage 1 AKI, limiting clinical significance. In our study, we found no differences in renal macro‐ or microcirculatory perfusion or oxygenation that could explain the increased incidence and severity of histological renal tubular injury.…”
Section: Discussionsupporting
confidence: 57%
“…Intra-operative administration of the a 2 -agonist, dexmedetomidine, has been reported to reduce the incidence of both AKI and delirium following cardiac surgery [7]. However, larger prospective studies have cast doubt on these findings [8,9]. Consequently, the role of dexmedetomidine in preventing these complications following cardiac surgery remains uncertain [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Delirium will be evaluated only once on day 1 after surgery, and twice daily (08:00-12:00 and 18:00-20:00) from days 2-7 after surgery by an independent follow-up staff team who will be blinded to group assignment using the Richmond Agitation Sedation Scale (RASS), and the Confusion Assessment Method for ICU (CAM-ICU). [32][33][34] The sedation status will be first assessed through RASS with a score ranging from −5 to +4. When the RASS score ≥-3, delirium will be evaluated.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…We read with interest the article by Wang et al which concluded that an intra-operative dexmedetomidine infusion did not decrease the incidence of delirium during the first 7 postoperative days in patients undergoing cardiac surgery, but might impair renal function, compared with placebo [1].…”
mentioning
confidence: 99%